PARTISIPASI PETANI, EFEKTIVITAS PROGRAM, DAN KONTRIBUSI BUMDES DALAM PEMBERDAYAAN EKONOMI (Agrienvi: Jurnal Ilmu Pertanian, 2021)
Village-owned enterprises have functioned as social and commercial institutions. BUMDes, as a legal entity, is formed based on the prevailing laws and regulations and must empower the community to improve welfare and independence according to the potential of each village. The research objective was to determine the effect of farmer participation, program effectiveness, and BUMDes contribution to the economic empowerment of farmers in Tanjungharjo Village, Kapas District, Bojonegoro Regency. This research used qualitative data with Structural Equation Modeling (SEM-PLS). The results showed that farmer participation did not have a significant effect on empowerment. In contrast, the effectiveness of the program and the contribution of BUMDes had a substantial impact on the economic empowerment of farmers in Tanjungharjo Village. Therefore, farmer participation must be increased to achieve farmer welfare and independence